Flipping the principal-agent model to foster host community participation in monitoring and evaluation of volunteer tourism programmes. Issue 3 (3rd July 2018) - Steele, Jessica; Scherrer, Pascal
ABSTRACT: This paper argues that stakeholder relationships in volunteer tourism represent principal-agent relationships. Using principal-agent (P-A) theory as a theoretical lens, this paper highlights types of relationships between host communities and volunteer tourism organisations most conducive for effective host community participation in the monitoring and evaluation of volunteer tourism programmes. Based on a survey of 80 organisations, followed by qualitative interviews with representatives from 29 organisations, the research concludes that 'flipping' or reversing the conventional P-A model opens up a new perspective on principal-agent relationships in volunteer tourism. This in turn highlights opportunities for facilitating more effective host community participation in monitoring and evaluation which is seen as an essential element to the sustainability of volunteer tourism.